Requirements-aware Models to Support Better Informed Decision-making for Self-adaptation using Partially Observable Markov Decision Processes - García Paucar, Luis Hernán (2019)
Descargue el texto completo en el repositorio institucional de la Aston University: https://doi.org/10.48780/publications.aston.ac.uk.00041929